Mechanochemical gold(III)-carbon bond formation - Eppel, Daniel; Eryiğit, Alpay; Rudolph, Matthias; Brückner, Margit; Rominger, Frank; Asiri, Abdullah Mohamed; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2021)
Starting from a [(MeOC^N^C)AuCl] complex as precursor, a direct substitution by C,H-activation from sp-, sp2- or sp3-C,H-bonds under basic conditions in a planetary ball mill was achieved. Because of the extraordinary photophysical properties of the target compounds, this protocol provides an easy access to a highly valued complex class. In contrast to existing protocols, no pre-functionalization of the starting materials is necessary and the use of expensive transition metal catalysts can be avoided, which makes this application appealing also for industrial purposes. In addition the methodology was not restricted to pincer complexes, which was demonstrated by the substitution of chelate type [(tpy)AuCl2] complexes.
Version of record online: May 6, 2021
Gesehen am 08.06.2021